O efeito Zeno no controle da evolução adiabática de um sistema quântico a partir de medidas não-seletivas - Calvello, Victor dos Santos (Universidade Federal de São Carlos, 2022)
The objective of the present work is to improve the performance of a Stimulated Raman Adiabatic Passage (STIRAP) in a 3-level system by applying successive non-selective measurements throughout the evolution (exploiting the properties of the quantum Zeno effect), so that a given quantum state is protected as the total time of evolution is decreased. This is a problem of great interest because it may take part in very important quantum techonologies such as the charging of quantum batteries and the optimization of Adiabatic Quantum Computing (AQC) processes. Through computer simulations it's been verified that it is possible to significantly reduce the total time of the population transfer via dark-state without taking the system off the adiabatic regime.
The Zeno effect in controlling the adiabatic evolution of a quantum system using non-selective measurements
Keywords: Teorema adiabático; Medidas quânticas; Tecnologias quânticas; Adiabatic theorem; Quantum measurements; Quantum techonologies; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL::FISICA CLASSICA E FISICA QUANTICA; MECANICA E CAMPOS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA ATOMICA E MOLECULAR